2017
DOI: 10.1007/978-3-319-49395-4_9
|View full text |Cite
|
Sign up to set email alerts
|

Plant Aquaporins and Abiotic Stress

Abstract: Festuca arundinacea and F. pratensis are the models in forage grasses to recognize the molecular basis of drought, salt and frost tolerance, respectively. Transcription profiles of plasma membrane intrinsic proteins (PIPs) and to-noplast intrinsic proteins (TIPs) aquaporin genes were obtained for leaves of Festuca species treated with different abiotic stimuli. F. arundinacea plants were exposed to drought and salt stress, whereas F. pratensis plants were cold-hardened. Changes in genes expression measured wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 134 publications
3
10
0
Order By: Relevance
“…In severe soil water deficit conditions (Ψ soil ≈ −0.30∼−0.50 MPa), the PIP2;5 OE maize lines may maintain root water uptake ability and leaf hydraulic conductance (Ding et al , 2020), resulting in similar or even higher plant transpiration and growth as in WT plants. Altogether, these data indicate that the beneficial effect of PIP2;5 overexpression is really dependent on water stress conditions and that, in mild water deficit, PIP2;5 OE lines perform better than control plants by faster stomatal closing and/or increased root water uptake ability, as previously observed for plants overexpressing other PIP aquaporins (Groszmann et al , 2017; Sade & Moshelion, 2017),…”
Section: Discussionsupporting
confidence: 81%
“…In severe soil water deficit conditions (Ψ soil ≈ −0.30∼−0.50 MPa), the PIP2;5 OE maize lines may maintain root water uptake ability and leaf hydraulic conductance (Ding et al , 2020), resulting in similar or even higher plant transpiration and growth as in WT plants. Altogether, these data indicate that the beneficial effect of PIP2;5 overexpression is really dependent on water stress conditions and that, in mild water deficit, PIP2;5 OE lines perform better than control plants by faster stomatal closing and/or increased root water uptake ability, as previously observed for plants overexpressing other PIP aquaporins (Groszmann et al , 2017; Sade & Moshelion, 2017),…”
Section: Discussionsupporting
confidence: 81%
“…ABA has been reported to affect the transcription of thousands of genes (Nemhauser et al, 2006) and is reported to have significant redundancy in its signal transduction pathway (Umezawa et al, 2010). Moreover, the ABA response varies in different tissues and under different environmental conditions (Saab et al, 1990;Sade and Moshelion, 2017). This complexity makes it hard to isolate the role of ABA in specific processes.…”
Section: Discussionmentioning
confidence: 99%
“…In soil-plant-atmosphere continuum system, water travels from soil to the atmosphere. Two water flow pathways are included in this process: axial movement (water flow from root xylem to leaf vessels) and radial movement (water flow from soil to root xylem and from leaf xylem vessels to mesophyll cells) ( Sade and Moshelion, 2017 ). The whole plant hydraulic conductance is determined by radial conductance, that is, root hydraulic conductivity (Lpr) and leaf hydraulic conductance (K leaf ), since water must pass through apoplastic barriers, which resist the water flow ( Steudle and Peterson, 1998 ; Sack and Holbrook, 2006 ).…”
Section: Drought Stress Affects Water Uptake and Transportmentioning
confidence: 99%
“…The whole plant hydraulic conductance is determined by radial conductance, that is, root hydraulic conductivity (Lpr) and leaf hydraulic conductance (K leaf ), since water must pass through apoplastic barriers, which resist the water flow ( Steudle and Peterson, 1998 ; Sack and Holbrook, 2006 ). During drought stress, both Lpr and K leaf are affected in higher plants ( Aroca and Ruiz-Lozano, 2012 ; Sade and Moshelion, 2017 ).…”
Section: Drought Stress Affects Water Uptake and Transportmentioning
confidence: 99%